Meta-Analysis: Effectiveness of Electroacupuncture in Reducing Anxiety and Depression - Yessy Widhi Astuti; Bhisma Murti; Hanung Prasetya (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Anxiety and depression can happen to anyone, especially in patients with certain diseases. Anxiety and depression can affect activity, and reduce quality of sleep, and life. Electroacupuncture is one of the therapies with small side effects to reduce anxiety and depression and provide a sedative effect. This study aims to analyze and estimate the effectiveness of electroacupuncture therapy to reduce anxiety and depression in patients based on the results of similar studies.Subjects and Method: This study used a systematic review and meta-analysis based on PICO, Population: Patients. Intervention: Electroacupuncture. Comparison: NonElectroacupuncture. Outcome: Decreased anxiety and depression. Data were obtained from Google Scholar, PubMed, Science Direct Hindawi, BMC, and Springer Link databases from 2010 to 2023. The search process used the keywords